EKSISTENSI MEREK JASA TERKENAL DALAM HUKUM NASIONAL DAN INTERNASIONAL - Riwanto, Nanda (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2020)
Trademark as an Intellectual property rights Â is a sign to distinguish between a product of goods or services in trade activity. In Explanation part of Article 21 paragraph (1) letter b Trademark Laws 2016, famous Trademark should be considered or can be characterized by: a. basic knowledge of the community towards the Trademark; b. Trademark reputation was earned through a vigorous campaign and spacious; c. trademark registration in several countries and the company's investments in other countries. Trademark Laws does not distinguish between the well-known trademark and famous Trademark. So that both well-known and famous trademark are still referred to as well-known trademark. Legal violations of trademark can be carried out by legal effortKeywords: well-known Trademark, famous Trademark,Â  and Legal Efforts